1984
DOI: 10.1254/jjp.34.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antinociceptive effect between the cyclic dipeptide cyclo (Tyr(Et)-homoarginine) and the linear dipeptide Boc-Tyr(Et)-homoarginine-OMe in rats.

Abstract: Abstract-The antinociceptive effect of the cyclic dipeptide cyclo[Tyr(Et)-homo arginine] (C.TEHA) was examined utilizing the tail flick test and the digitus pinching test in rats in comparison with the linear dipeptide Boc-Tyr(Et)-homoarginine OMe (B.TEHM).Though both dipeptides administered into the lateral, 3rd and 4th cerebroventricles produced antinociceptive effects equipotent to morphine, except for the 4th cerebroventricular administration of B.TEH M, the administration into the spinal subarachnoid spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Since the isolation and identification of dermorphin in skin extracts of the Brazilian frog (Montecucchi et al, 1981a,b), evidence has accumulated that several other naturally occurring and synthetic peptides have narcotic-like pharmacological activity Broccardo et al, 1981;Sato et al, 1984a;1985). The sequence of dermorphin was determined to be Tyr-D-Ala-Phe-Gly-Tyr-Pro-Ser-NH2 (Montecucchi et al, 1981 a) and it was found to have pronounced opioid antinociceptive activity (Broccardo et al, 1981;Sato et al, 1984b).…”
Section: Introductionmentioning
confidence: 99%
“…Since the isolation and identification of dermorphin in skin extracts of the Brazilian frog (Montecucchi et al, 1981a,b), evidence has accumulated that several other naturally occurring and synthetic peptides have narcotic-like pharmacological activity Broccardo et al, 1981;Sato et al, 1984a;1985). The sequence of dermorphin was determined to be Tyr-D-Ala-Phe-Gly-Tyr-Pro-Ser-NH2 (Montecucchi et al, 1981 a) and it was found to have pronounced opioid antinociceptive activity (Broccardo et al, 1981;Sato et al, 1984b).…”
Section: Introductionmentioning
confidence: 99%